2022
DOI: 10.1108/ijshe-07-2021-0308
|View full text |Cite
|
Sign up to set email alerts
|

Do professional courses prepare hospitality students for efficient surplus food management? A self-evaluation of professional competence in food waste prevention

Abstract: Purpose This study aims to examine Taiwanese hospitality students’ self-reported professional competence in surplus food management and assess the usefulness of their university training in this area. Using the importance-performance analysis (IPA) method, it is possible to obtain a clearer understanding of the priority order of the items that require improvement and to identify which surplus food management competence items should be strengthened in the school curriculum and which items should be enhanced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Analyzing the characteristics and application scope of big data technology is the premise and guarantee for the application of intelligent means in moral education courses in universities. Combined with big data technology, moral education courses in colleges can form transparent and efficient curriculum design scheme and evaluation annotation [13,14]. Because the CNN method designed in this paper is only applied to moral education courses in colleges and universities, and the characteristics of moral education courses in primary and secondary schools are quite different from those in colleges and universities.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the characteristics and application scope of big data technology is the premise and guarantee for the application of intelligent means in moral education courses in universities. Combined with big data technology, moral education courses in colleges can form transparent and efficient curriculum design scheme and evaluation annotation [13,14]. Because the CNN method designed in this paper is only applied to moral education courses in colleges and universities, and the characteristics of moral education courses in primary and secondary schools are quite different from those in colleges and universities.…”
Section: Introductionmentioning
confidence: 99%
“…Zabłocka et al [ 36 ], in a study of natural science college students including those with nutritional knowledge, also indicated a high percentage of familiarity with date labels. Their behavior was also correlated with good knowledge of food storage [ 64 ]. Broshius’ [ 96 ] study found some discrepancies in respondents’ answers about expiration dates and food storage.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to conduct further research and analysis. Ko and Lu [ 64 ], on the other hand, said that education in the human-nutrition and food-service professions helps manage leftover food. Students with an increased interest in food and food waste are more likely to avoid throwing food away [ 65 ].…”
Section: Introductionmentioning
confidence: 99%